Low-intensity pulsed ultrasound reduces lymphedema by regulating macrophage polarization and enhancing microcirculation - Liu, Zihao; Li, Jia; Bian, Yu; Zhang, Xiaojie; Cai, Xiaojun; Zheng, Yuanyi (Frontiers in Bioengineering and Biotechnology, 2023)
Background: Conventional therapies reduce lymphedema but do not cure it because they cannot modulate the pathophysiology of secondary lymphedema. Lymphedema is characterized by inflammation. We hypothesized that low-intensity pulsed ultrasound (LIPUS) treatment could reduce lymphedema by enhancing anti-inflammatory macrophage polarization and microcirculation. Methods: The rat tail secondary lymphedema model was established through the surgical ligation of lymphatic vessels. The rats were randomly divided into the normal, lymphedema, and LIPUS treatment groups. The LIPUS treatment (3 min daily) was applied 3 days after establishing the model. The total treatment period was 28 days. Swelling, fibro adipose deposition, and inflammation of the rat tail were evaluated by HE staining and Masson’s staining. The photoacoustic imaging system and laser Doppler flowmetry were used to monitor microcirculation changes in rat tails after LIPUS treatment. The cell inflammation model was activated with lipopolysaccharides. Flow cytometry and fluorescence staining were used to observe the dynamic process of macrophage polarization. Results: After 28 days of treatment, compared with the lymphedema group, the tail circumference and subcutaneous tissue thickness of rats in the LIPUS group were decreased by 30%, the proportion of collagen fibers and the lymphatic vessel cross-sectional area was decreased, and tail blood flow was increased significantly. Cellular experiments revealed a decrease in CD86+ macrophages (M1) after LIPUS treatment. Conclusion: The transition of M1 macrophage and the promotion of microcirculation could be responsible for the beneficial effect of LIPUS on lymphedema.